Zmiany zawartości form fosforu oznaczonych w gruntach pokopalnianych z rejonu Łęknicy = Changes of phosphorous forms content in post-mining grounds in Łęknica locality - Greinert, Henryk; Greinert, Andrzej; Drab, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In presented paper the results of phosphorus content in the post-mining grounds from the Łęknica locality, analyzed with the Egner-Riehm method, in 0,1M HCl extract and subtotal form have been described. The content of appointed phosphorus forms, with except of top horizons, was very low. Phosphorus form content, appointed in the Egner-Riehm extract has been especially low. Causes of this were exceptionally unfavourable proprieties of soils, in large measure caused by the pyrite presence in them, strongly acidifying dumped material.
Keywords: fosfor glebowy; rekultywacja leśna; grunt pogórniczy; phosphorous in soils; forest reclamation; post-mining areas